The Role of Informal Digital Learning of English (IDLE) in Enhancing EFL Students' Language Skills and Digital Literacy in Higher Education - Yaqutil Ummi Rohimah; Siti Mariam; Lulut Widyaningrum (Language and Education Journal, 2026)
The development of digital technology has significantly impacted English language education, with students increasingly turning to Informal Digital Learning of English (IDLE) through platforms such as YouTube, TikTok, and mobile applications. This study aimed to investigate EFL students' IDLE practices and examine IDLE's role in enhancing their language skills and digital literacy in higher education. Employing a mixed-methods approach with a descriptive design, this study involved 43 undergraduate students from an English Language Education program at UIN Walisongo Semarang, Indonesia, selected through purposive sampling. Data were collected via an online questionnaire comprising 17 Likert-scale items and 3 open-ended questions and analyzed using descriptive statistics and thematic analysis. The findings showed that students were highly engaged in IDLE, particularly through bite-sized content on social media and YouTube. Moreover, IDLE significantly contributed to students' language skills, including vocabulary, listening, and speaking, as well as digital literacy skills such as confidence in navigating digital platforms and evaluating online information. This study highlighted IDLE as a meaningful bridge between informal and formal learning, fostering independent and digitally competent EFL learners.